Cycling of mercury in the environment: Sources, fate, and human health implications: A review. Issue 9 (3rd May 2017) - Beckers, Felix; Rinklebe, Jörg
ABSTRACT: Mercury (Hg) is ubiquitary, naturally enriched in volcanic regions, and has wide applications in science, industry, and agriculture. Recently, the increasing awareness of Hg toxicity has led to the replacement of Hg in many areas; however, anthropogenic activities such as coal burning and smelting of metal ores continue to release large amounts of Hg into the environment. In particular, the atmospheric distribution of the highly volatile Hg around the globe can result in the pollution of pristine regions without local emission sources. The chemical speciation of Hg determines its mobility and toxicity; in flooded soils and sediments, microbial methylation can occur. Bioaccumulative (mono)methylmercury (MeHg; CH3 Hg + ) can affect human health particularly via the consumption of contaminated fish and rice since methylmercury is a potent neurotoxin. Also, elemental Hg vapor is harmful for the central nervous system, while inorganic Hg compounds primarily affect the kidney. This review summarizes recent knowledge on the behavior of Hg in soils and sediments as well as in other environmental elements including implications on human health and discusses future research needs.